The Legal Status Issue of Unmanned Maritime Vehicles (UMVs) Used for Military Purposes - Bahadır, Levent (Journal of Applied And Theoretical Social Sciences, 2023)
In parallel with the advances in technology, the use of unmanned vehicles on the battlefield for military purposes is becoming increasingly widespread. Since the beginning of the new millennium, the undeniable contributions of Unmanned Aerial Vehicles (UAVs) in combat and combat support operations, especially in Afghanistan and Iraq, have made these vehicles indispensable for states, while on the other hand, it has affected the expansion and deepening of the range of missions of unmanned vehicles used in the maritime environment within a limited framework. However, the use of UMVs, which are gaining importance for states day by day and becoming a force multiplier, has also brought along some legal debates. The absence of a provision directly related to UMVs in international maritime law legislation has led to the emergence of grey areas regarding the legal status of these vehicles. Since the increasingly sophisticated UMVs in terms of size, tonnage and level of autonomy diversify in a wide spectrum, not all UMVs will be subject to the same legal status naturally. On the other hand, the problem of legal status becomes more complex as the states take steps towards establishing their national legislation. Based on the provisions of the 1982 United Nations Convention on the Law of the Sea (UNCLOS), it is important to discuss UMVs to understand the potential legal status of these instruments, which are directly related to critical issues such as freedom of navigation, belligerent rights and judicial immunity.